2022
DOI: 10.3389/fimmu.2022.974864
|View full text |Cite
|
Sign up to set email alerts
|

Variable frequencies of peripheral T-lymphocyte subsets in the diabetes spectrum from type 1 diabetes through latent autoimmune diabetes in adults (LADA) to type 2 diabetes

Abstract: T lymphocytes are key players in the pathogenesis of autoimmune diabetes. We recruited subjects with T1D (n=81), LADA (n=82), T2D (n=95) and NGT (n=218) and analyzed the percentages of T-lymphocyte subsets, including T helper 1 (Th1), T helper 2 (Th2), T helper 17 (Th17), T cytotoxic 1 (Tc1), regulatory T cells (Tregs), effector T (Teff), naïve T, central memory T (Tcm), and effector memory T (Tem) cells by flow cytometry. LADA patients possessed similar frequencies of IFN-γ+CD4+ T (Th1), IFN-γ+CD8+ T and CD4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…In the past, more attention has been paid to the regulation of insulin sensitivity by innate immune cells, particularly macrophage mediated, which have been mentioned before. Cells of the adaptive immune system, B lymphocytes and T lymphocytes, and their respective subsets, are also thought to be important regulators of glucose homeostasis and play an important role in the immunopathogenesis of autoimmune diabetes ( 168 , 173 , 174 ). Studies have shown that CD4(+) T lymphocytes in visceral adipose tissue (VAT) control the progression of metabolic abnormalities associated with obesity, including expansion of adiposity and pathogenic VAT T cells, which can be successfully reversed by immunotherapy ( 175 , 176 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…In the past, more attention has been paid to the regulation of insulin sensitivity by innate immune cells, particularly macrophage mediated, which have been mentioned before. Cells of the adaptive immune system, B lymphocytes and T lymphocytes, and their respective subsets, are also thought to be important regulators of glucose homeostasis and play an important role in the immunopathogenesis of autoimmune diabetes ( 168 , 173 , 174 ). Studies have shown that CD4(+) T lymphocytes in visceral adipose tissue (VAT) control the progression of metabolic abnormalities associated with obesity, including expansion of adiposity and pathogenic VAT T cells, which can be successfully reversed by immunotherapy ( 175 , 176 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…This suggests that RPS26 might play a role in the development and progression of type 1 diabetes mellitus through its involvement in ER stress. However, autoimmunity is correlated with the pathogenesis of both type 1 diabetes mellitus and LADA, and T lymphocytes are crucial for this process 41 . Previous studies have shown that RPS26 is highly expressed in T lymphocytes, and that the ablation of RPS26 in T lymphocytes disrupts peripheral T lymphocyte homeostasis and impairs T lymphocyte development in the thymus 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Latent autoimmune diabetes in adults is an autoimmune-mediated type of diabetes, and T lymphocytes are a key factor in its pathogenesis [ 14 ]. Data demonstrates that, based on these T-cell subset alterations, IR may be involved in the pathogenesis of LADA [ 15 ]. Positive correlations between the serum levels of autoantibodies and pancreatic islet dysfunction in the autoimmune disease model of mice may partially reflect the relationship between autoimmunity and LADA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%